2011
DOI: 10.1007/s00024-011-0342-y
|View full text |Cite
|
Sign up to set email alerts
|

Ion Composition of Fog Water and Its Relation to Air Pollutants during Winter Fog Events in Nanjing, China

Abstract: Intensive field experiments focused on fog chemistry were carried out in the northern suburb of Nanjing during the winters of 2006 and 2007. Thirty-seven fog water samples were collected in nine fog events. Based on the chemical analysis results of those samples and the simultaneous measurements of air pollution gases and atmospheric aerosols, the chemical characteristics of fog water and their relations with air pollutants during fog evolution were investigated. The results revealed an average total inorganic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Sulfate is the predominant acidifying pollutant of fog water at many sites in Asia (Kim et al, 2006;Li et al, 2011;Yang et al, 2011). It is formed by atmospheric oxidation from its precursor sulfur dioxide (SO 2 ).…”
Section: Ion and Metal Concentrations In Fog Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfate is the predominant acidifying pollutant of fog water at many sites in Asia (Kim et al, 2006;Li et al, 2011;Yang et al, 2011). It is formed by atmospheric oxidation from its precursor sulfur dioxide (SO 2 ).…”
Section: Ion and Metal Concentrations In Fog Watermentioning
confidence: 99%
“…The collection of fog is quite challenging and time consuming. Nevertheless, numerous studies investigated the chemical composition of fog in the United States (e.g., Collett et al, 1999a, b;Collett et al, 2002;Herckes et al, 2015), in Europe (e.g., Wrzesinsky and Klemm, 2000;Polkowska et al, 2008;Giulianelli et al, 2014;Wang et al, 2015), and in Asia (e.g., Tago et al, 2006;Kim et al, 2006;Watanabe et al, 2006;Lu et al, 2010;Watanabe et al, 2010;Li et al, 2011;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a broader context covering East Asia, the chemical composition of fog water has been studied in Taiwan (Liang et al, 2009;Simon et al, 2016), Japan (Minami and Ishizaka, 1996;Aikawa et al, 2005;Watanabe et al, 2011), South Korea (Kim et al, 2006), on Mount Taishan in the North China Plain Guo et al, 2012), on central Chinese Mount Heng (Sun et al, 2010), in Shanghai (Li et al, 2011), Nanjing (Tang et al, 2008;Lu et al, 2010;Yang et al, 2012), Eastern China (Desyaterik et al, 2013), and in Ji'an, Southeast China (Wang et al, 2014). Many of these studies showed that anthropogenic emissions strongly influence the fog chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…It is not only the gaining importance of other topics such as greenhouse gas concentrations and chemistry, or the rapid development of instrumentation and remote sensing techniques to study more substances and to develop better spatial coverage of atmospheric conditions, but also the increase of the pH of precipitation water that lead to the presumption that acid precipitation loses relevance. The observed increase of the pH is partly due to the decreasing emissions of acidity precursors, namely sulfur dioxide (SO2), which is oxidized to H2SO4 in the atmosphere, and nitrogen oxides (NOx), which are oxidized to HNO3, and partly due to the increasing importance of ammonia (NH3) acting as a neutralizer in the atmospheric water phase (clouds, fog, rain) through the formation of the ammonium ion (NH4 + ) [1][2][3]. Therefore, the pH itself, which is an intensity measure, is nowadays less a key indicator for the pollution level the atmospheric water phase than it was earlier: High emissions of acidity precursors (SO2, NOx) may be, partially or fully, balanced out by high emissions of the neutralizer NH3.…”
Section: Introductionmentioning
confidence: 99%
“…High emissions of air pollutants including precursors of atmospheric acidity lead to low pHs of rain, clouds, and fog (e.g., [4][5][6][7][8]) and to highly acidic aerosol particles (e.g., [9,10]). However, there are also reports of high pHs (above 5.0) in precipitation, cloud, and fog water (e.g., [1,11]). While the neutralizing action of ammonia, and, in some cases, from calcium, plays an important role also in this part of the world, some of the reports indicate that rather clean, un-polluted cases of rain and fog were found [6,8,12].…”
Section: Introductionmentioning
confidence: 99%